Workplace Transformation: Strategies for Employee Voice and Communication in Organizational Management - Jamaludin, Maisarah Auni; Mohd Salleh, Kahirol; Sulaiman, Nor Lisa; Parasuram, Balakrishnan; Al-Asfour, Ahmed (Journal of Technical Education and Training, 2025)
Employee voice and communication in the workplace are crucial for allowing employees to express dissatisfaction, ideas, concerns, suggestions, or recommendations. This study focuses on the essential aspects of employee voice and communication in promoting a positive workplace environment among employees and management within organizations in Malaysia. The study aims to investigate organizational management’s insights and perspectives on effective strategies for fostering employee voice and enhancing communication in the workplace. Effective employee voice and communication can significantly influence how employees feel about issues that directly affect them, such as miscommunication, discrimination, oppression, dissatisfaction, and lack of motivation. This study employed a basic interpretative qualitative methodology to gain insights and opinions from Technical and Vocational Education and Training (TVET) representatives including the Malaysian Employers Federation (MEF), the Malaysian Trades Union Congress (MTUC), and the Union Network International Malaysia Labour Centre (UNI-MLC) regarding the concept of employee voice and communication in the Malaysian context. Data were obtained through interview sessions, and thematic categorization was conducted based on the coding process. The findings of the study emphasized three important aspects: fundamentals, channels, and legal governance in improving employee voice and communication in the workplace. This study not only highlights the employees’ right to voice their concerns but also underscores the importance of organizational management recognizing employee voice and communication as key to achieving productivity and maintaining strong working relationships at all levels of the organization. Additionally, incorporating TVET can further enhance these efforts by equipping employees with the necessary skills and knowledge to effectively participate in and contribute to workplace discussions, thereby fostering a more inclusive and dynamic organizational culture.